Comparison of infrared thermography of the blowhole mucosa with rectal temperatures in killer whales (Orcinus orca) - Russell, Jennifer P.; Germain, Micah St.; Osborn, Steve D.; Schmitt, Todd L.; Herrick, Kelsey E. S.; Robeck, Todd (Frontiers in Marine Science, 2024)
Killer whales are an important sentinel species and developing non-invasive methods of health assessments might provide insight for understanding how wildlife health is influenced by ecosystem change. Rectal temperature (RT) is a proxy for core body temperature in managed-care cetaceans, however, this measurement is impractical for free-ranging cetaceans and infrared imaging has been suggested as an alternative. The aim of the current study was to prospectively compare infrared thermography of the blowhole to rectal temperatures in killer whales, as well as establish a healthy range for rectal temperature using retrospective data. Infrared video was recorded from the blowhole of thirteen healthy killer whales in managed care, immediately followed by rectal temperature measurement. Repeated measures Bland-Altman analysis revealed blowhole temperature (BHT) had a bias of -1.28°C from RT. Considerable proportional bias was observed with agreement between measurements improving as mean temperature increased. RT positively associated with air temperature, and inversely associated with body mass. BHT was not significantly affected by sex or body mass but was significantly affected by water temperature and air temperature. Retrospective analysis from eighteen killer whales (n = 3591 observations) was performed to generate expected RT ranges, partitioning out for sex and body mass. Given the proportional bias observed with Bland Altman analysis, BHT cannot currently be recommended as a measurement for absolute core body temperature, however infrared thermography of the blowhole remains a promising tool for health assessment of free-ranging killer whale populations, as it may serve as a non-contact screening tool to detect pyrexic animals within a group.